Dynamic balancing of RECOVER robotic system. Issue 1 (December 2020) - Nadas, I.; Gherman, B.; Bîrlescu, I.; Bogateanu, R.; Banica, A.; Carbone, G.; Pisla, D.
Abstract: This paper presents a novel robotic system for the lower limb rehabilitation of post-stroke survivors. The model presented in this paper aims to demonstrate an innovative solution that helps in the mobilization of the hip and knee flexion/extension and the ankle plantar flexion/extension and eversion/inversion motions. The paper focuses on achieving the dynamic balancing of the hip-knee module, which due to high accelerations peak values and large size is prone to a certain degree of instability, leading to shaking forces and unwanted vibration that might reduce the safety feelings of the patient. A dynamically balanced mechanism will reduce noise, wear and fatigue and allow higher payload capacity.